Sequencing and analysis of complete genome of the attenuated Hanvet1.VN strain used for vaccine production against porcine reproductive and respiratory syndrome - Nga, Nguyễn Thị; Thu, Hà Thị; Hoa, Nguyễn Thị; Hiền, Vũ Thị; Thu Hiền, Trần Thị; Khánh, Trần Vân; Ba, Nguyễn Thanh; Vũ, Nguyễn Hữu; Quyền, Đồng Văn; Thành, Tô Long; et al. (Vietnam Journal of Biotechnology, 2018)
The porcine reproductive and respiratory syndrome virus (PRRSV) attenuated strain Hanvet1.VN has been developed by the Pharmaceutical and Veterinary Material J.S.C (HANVET) by passaging HY-2010 strain on MARC-145 cells for 80 passages and used for PRRS vaccine production. In this study, we sequenced and analyzed the whole genome of the attenuated Hanvet1.VN strain. The total RNA was extracted from the Hanvet1.VN strain, RT-PCR was used for amplification of 15 separate segments of the whole genome. The amplified segments were cloned into the pCR2.1 vector and sequenced by Sanger sequencing. The sequences were analyzed with BioEdit and DNA Star Software. The results showed that, GP5 of the Hanvet1.VN attenuated strain had 100% identity in amino acid (aa) sequences with one of the pathogenic Vietnamese strain isolated in Quang Nam Province and had 98% identity with that of the Chinese 07NM strain. However, the identity of aa sequence of the Hanvet1.VN GP5 was much lower in the comparison with GP5 of VR2332, and it was only 87%. The MP and NP proteins were highly conserved compared with pathogenic strains circulating in Vietnam (07QN) and China (07NM) (99-100%, respectively). The other eight proteins of the Hanvet1.VN strain showed changes from 1.2% in NP1a to 3.9% in GP2 compared with the 07QN strain. However, the aa identity of all Hanvet1.VN proteins were very low when compared with proteins of PRRSV type II strain (North American strain, VR2332), ranged from 86.25% to 97.7%. Our results showed that the Hanvet1.VN attenuated vaccine strain had protective immunogenicity similar to that strain circulating in Vietnam closely related to a strain from China but different from the type II North American strain VR2332. Hence, for importing PRRSV vaccine, especially from American or Europe Countries, antigenic compatibility of the PRRSV vaccine and strains circulating in Vietnam should be concerned in PRRSV vaccine production.